Mobile Robot Framework Designing and Transferring of Data by PCI Controller - Alireza Rezaee (Institute of Advanced Engineering and Science, 2016)
In this paper, a differential robot is designed and controlled by PCI card. This card connected between personal computer and microcontroller. Furthermore PID controller was designed by Asic device and implemented on robot.In this paper, instead of using that massive hardware’s, it designed a single FPGA chip to perform the same motion control of robot wheels. We developed a general purposed motion control of robot using a field programmable gate array (FPGA).In order to obtain independent robots movement, the main PID controller is implemented with a Field Programmable Gate Array. The main PID controller routine was designed to be fairly general purpose and modular form. While it is used to control a DC motor, it could be re-deployed to other situations where some parameter has to be controlled to a set value under varying conditions. The actual control software is located in a single function and its major inputs and output are held in a structure. Although it was designed originally for a specific job it is really only intended as an example of the basic techniques involved and to allow those with no control system knowledge to experiment with a simple PID system., FPGA, ATmega128L, Robot, Digital.